2017
DOI: 10.1021/acscatal.7b02647
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Evidence for Ligand-Centered Electrocatalytic Oxygen Reduction with the Conductive MOF Ni3(hexaiminotriphenylene)2

Abstract: Establishing catalytic structure−function relationships introduces the ability to optimize the catalyst structure for enhanced activity, selectivity, and durability against reaction conditions and prolonged catalysis. Here we present experimental and computational data elucidating the mechanism for the O 2 reduction reaction with a conductive nickel-based metal−organic framework (MOF). Elucidation of the O 2 reduction electrokinetics, understanding the role of the extended MOF structure in providing catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
165
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(169 citation statements)
references
References 23 publications
3
165
0
1
Order By: Relevance
“…[1,2] Recently, there are growing interests in design and synthesis of 2D covalent or noncovalent organic materials with in-plane π-conjugation structure. [17][18][19][20][21][22][23][24][25][26][27][28][29] The planar structure of these graphene analogues facilitates the synthesis of benzene-and triphenylene-polyselenols and CPs containing these ligands (relevant results are in preparation). [17][18][19][20][21][22][23][24][25][26][27][28][29] The planar structure of these graphene analogues facilitates the synthesis of benzene-and triphenylene-polyselenols and CPs containing these ligands (relevant results are in preparation).…”
Section: Coordination Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Recently, there are growing interests in design and synthesis of 2D covalent or noncovalent organic materials with in-plane π-conjugation structure. [17][18][19][20][21][22][23][24][25][26][27][28][29] The planar structure of these graphene analogues facilitates the synthesis of benzene-and triphenylene-polyselenols and CPs containing these ligands (relevant results are in preparation). [17][18][19][20][21][22][23][24][25][26][27][28][29] The planar structure of these graphene analogues facilitates the synthesis of benzene-and triphenylene-polyselenols and CPs containing these ligands (relevant results are in preparation).…”
Section: Coordination Polymersmentioning
confidence: 99%
“…The synthesis of protected BHS hexakis(tertbutylseleno)benzene (t-Bu 6 BHS) was reported by Turner and Vaid in 2012. [17][18][19][20][21][22][23][24][25][26][27][28][29] The planar structure of these graphene analogues facilitates the [33] An alternative approach is Lewis acid promoted deprotection protocol.…”
mentioning
confidence: 99%
“…Copyright 2016, Nature Publishing Group. F) CV curves under O 2 atmosphere at pH 13, pH 8, and pH 4, and G) reaction mechanism of the 2‐electron transfer pathway for Ni 3 (hitp) 2 towards ORR . Copyright 2017, American Chemical Society.…”
Section: Classification Of Mof‐based Orr Catalystsmentioning
confidence: 99%
“…As shown in Figure E, Ni 3 (hitp) 2 has a honeycomb‐like layered structure and exhibits good electrocatalytic activity in an extensive range of pH value (4–13) (Figure F). Intensive research indicated that Ni 3 (hitp) 2 catalyzed oxygen reduction through a two‐electron pathway by the ligands as active sites rather than metal centers (Figure G) . This mechanism shows the importance of electron delocalization for accessing key intermediates and should be applicable for designing other conductive MOFs.…”
Section: Classification Of Mof‐based Orr Catalystsmentioning
confidence: 99%
“…Dincă’s group have synthesized a series of two‐dimensional conductive MOFs including M 3 (HIB) 2 and M 3 (HITP) 2 (M=Cu, Ni; HIB=hexaiminobenzene; HITP=2,3,6,7,10,11‐hexaiminotriphenylene) and unveiled a reasonable activity of the Ni 3 (HITP) 2 in catalysing ORR . They have further indicated the β‐C on the HITP ligand, rather than the metal centre, and the delocalized valence band in the 2D framework synergistically contribute to the ORR activity . Yoon et al.…”
Section: Introductionmentioning
confidence: 99%